Konsep harta menurut perspektif undang-undang islam dan undang-undang sivil : satu tinjauan - Yazid Ahmad,; Hj. Ibnor Azli Ibrahim, (Universiti Kebangsaan Malaysia, 2006)
‘Property’ played an important role and have a significant influence in human life. For that purpose, this article will examines the concept of ‘property’ according to Islamic law based upon the Holy Qur’an and views from muslim scholars and its comparison with civil law